A Character Centered Analysis of Anna’s Personal Development in the Film My Oxford Year - Fauzi, Fera Fitri; Adiningsih, Sekar Safitri Dhita; Rosalinah, Yanti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This research focuses on “A Character-Centered Analysis of Anna’s Personal Development in the film My Oxford Year.” The purpose of the study is to examine how Anna, as the main character, is portrayed and how her personal development unfolds throughout the film. The data were obtained from the depiction of Anna in various scenes, including her dialogue, actions, emotional expressions, and interactions with other characters. To analyze these elements, the study employs Murphy’s (1972) theory of characterization, which provides a framework for understanding how a character is shaped within the narrative. Using a qualitative descriptive method, the researcher observed the film repeatedly and took detailed notes to identify patterns related to Anna’s growth. The findings indicate that Anna’s development appears through several dimensions of her characterization, including her changing decisions, emotional responses, and evolving perspectives as she navigates new experiences at Oxford. The analysis reveals that Anna undergoes growth in three major areas. First, emotional development, shown through her increasing maturity in managing conflicts and personal challenges. Second, relationship development, reflected in her ability to form meaningful connections and reassess her priorities. Third, identity formation, as she begins to understand her values, ambitions, and sense of purpose more clearly. Overall, the study concludes that Anna’s journey in My Oxford Year represents a gradual and realistic process of personal transformation. Her growth is shaped by the challenges, opportunities, and responsibilities she encounters, illustrating a nuanced portrayal of character development within the film.